ANALISIS BIBLIOMETRIK PENELITIAN KESEHATAN REPRODUKSI REMAJA: TREN, TOPIK, DAN KOLABORASI GLOBAL DALAM DUA DEKADE TERAKHIR - Anggraini, Yeni; Utami, Uji (Jurnal Ilmiah Maternal, 2025)
Adolescent reproductive health is a strategic issue in global health development, as reproductive problems during adolescence significantly impact quality of life, education, and future productivity. Bibliometric analysis is essential to map research trends and identify the dominant topics in the global scientific literature. This study aims to analyze publication trends, author collaboration networks, and dominant keywords in adolescent reproductive health research using a bibliometric approach. A comprehensive search was conducted in the Scopus database using the keyword “adolescent reproductive health” for publications from 2000 to 2024. Data were analyzed using VOSviewer software to generate visual maps of collaboration and keyword co-occurrence. A total of 1,284 articles were identified. There has been a significant increase in publications since 2015. Major contributing countries include the United States, India, and Indonesia. Dominant keywords include "contraception", "sexual education", and "pregnancy prevention". There is a growing global interest in adolescent reproductive health, but geographic disparities in research collaboration remain. These findings provide valuable insights for policymakers and researchers in developing future intervention strategies and research priorities.